DETERMINANTS OF CORPORATE BOND AND SUKUK RATINGS IN INDONESIA - Afifatun Ni’mah; Nisful Laila; Sylva Alif Rusmita; Eko Fajar Cahyono (Bank Indonesia, 2020)
This study aims to determine the factors, both financial and non-financial, which influence corporate bond and Sukuk ratings. The results will be useful for companies, investors or related parties as additional information and references for their investment decisions. Using ordinal logistic regression models with SPSS version 21 software, the study analyses the determinants of corporate bond and sukuk ratings listed on the Indonesia Stock Exchange (IDX) for the period 2013-2017. The variables employed are profitability, liquidity, leverage, company size, securities structure and maturity date. The results of the Wald test statistics show that leverage ratio, firm size, security structure, and maturity date are the factors that influence the probability of high or low corporate bond ratings, while profitability and liquidity ratios are factors that have no effect on the level of such ratings. With regard to sukuk, profitability, liquidity, and maturity date are the factors that influence the probability of high or low corporate sukuk ratings, while leverage ratio, company size, and security structure have no effect on the ratings.